It's not a sprint, it's a marathon: reviewing governmental R&D support for environmental innovation - Leonie P. Meissner; Sonja Peterson; Finn Ole Semrau (Journal of Environmental Planning and Management, 2024)
In a race against global warming, the world must accelerate the development and adoption of environmental innovations (EIs). In this literature review, we explore the role of governments in promoting EIs across stages of maturity and assess the potential to reduce emissions. Theoretical frameworks on market imperfections underline the necessity of governmental Research and Development (R&D) support. While emission pricing remains the most cost-efficient climate policy, it fails as a stand-alone instrument to sufficiently encourage EI. Overall, the optimal approach is a policy mix complementing emission pricing with governmental R&D support. The theoretical finding is backed by empirical studies on the developmentand deployment of renewable energies, which also show that investment in R&D can effectively reduce emissions. The review concludes by dissecting two pivotalpolicy initiatives, the US Inflation Reduction Act and the European Green New Deal Industrial Plan, evaluating their potential to effectively contribute to decarbonization.
Keywords: O32; O38; Q54; Q55; Q58; 330; green/eco-/environmental innovation; R&D support; climate policy; innovation policy